Semiotic exploration of Indian patriarchy: Roland Barthes' perspective on Gangubai Kathiawadi - Gunadi, Andini Damayanti; Azwar, Azwar (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2024)
This study delves into the profound impacts films can exert on audiences. Through an in-depth exploration of the Gangubai Kathiawadi film, it endeavors to unveil the intricate layers of patriarchal culture prevalent in Indian society. Employing Roland Barthes's Semiotics as a guiding framework, the research meticulously examines the semiotic elements of signs, denotations, connotations, and myths embedded within the movie. To ensure the robustness of the findings, a multifaceted approach to data collection and analysis was adopted. The primary data source, the Gangubai Kathiawadi movie itself, was the cornerstone. Additionally, secondary data sources, including literature reviews and interviews with domain experts, were strategically utilized to triangulate perspectives and enrich the analysis. The meticulous triangulation of data sources ensures the reliability and validity of the findings, thereby enriching our understanding of the intricate interplay between film representations and societal constructs. The methodology employed in this research is anchored in descriptive qualitative techniques, wherein scene-by-scene analysis units are meticulously scrutinized for insights. By employing this methodological rigor, the study endeavors to unravel the patriarchal representations depicted in the film. The research findings illuminate a spectrum of patriarchal constructs within the Gangubai Kathiawadi, including stereotypical gender categorizations, instances of subordination and objectification of women, and systemic injustices faced by prostitutes. The film adeptly portrays the entrenched societal norms that perpetuate the superiority of men and the inferior status accorded to women. Through its compelling portrayal, Gangubai Kathiawadi emerges as a poignant reflection of societal attitudes towards women, particularly within the context of Indian society.